The Guidelines for the Formation of Accounting Provision for the Management of Processes of Implementing a Concession Agreement - Kovalchuk Volodymyr V. (Bìznes Inform, 2018)
The article analyzes the works which constitute the basis of development of organizational guidelines of accountance of operations under concession agreement. It is determined that the problems of accounting of operations under the concession agreement were not raised in the domestic accountance. Arranging the information links is essential to establish a set of objects for the accounting display and the fulfillment of terms of a concession contract. An information model of interaction between the concessionary and the concessionaire is constructed, and a characterization of the specified information model is provided. The proposed model comprises: announcement of competition for participation in a project of public-private partnership, implemented in the form of concession; submission of documents for participation in the competition for substitution of private partner – concessionaire; conclusion of concession contract; transfer of the concession object; settlement of concession payments; obtaining financial results from performing the concession activity by private partner. It should be noted that an important component is identification of all possible objects of accountance at the stage of transfer of the concession object. In turn, the order of the accounting display at the newly created enterprise and at the existing one will differ.